EFFECT OF RECYCLED FINE AGGREGATE ON PROPERTIES OF MORTAR - Wei Ning; Xiuwen Lv (Ceramics-Silikáty, 2023)

(untitled)
To improve the utilisation rate of recycled fine aggregate (RFA), five different replacement rates of RFA were used in this article. Recycled mortar (RM) was used as the research object to test its consistency, compressive strength, flexural strength, chloride ion migration coefficient, and frost resistance. Thermal analysis (TG) and scanning electron microscopy (SEM) were used to analyse the hydration products and microstructure of the mortar. Using RM as the research object, tests were conducted on the consistency, compressive strength, flexural strength, resistance to chloride ion migration coefficient, and frost resistance. TG and SEM were used to analyse the hydration products and microstructure of the mortar. The results showed that the higher the RFA replacement rate, the lower the RM consistency. When the replacement rate is 30%, the RM has better mechanical properties than the natural mortar (NM); when the RFA increases the chloride ion migration coefficient and its replacement rate exceeds 30%, the frost resistance of the RM decreases, and the strength loss rate increases significantly; the TG analysis showed that as the RFA replacement rate increased, the CH content decreased and the CaCO₃ content increased; the SEM analysis shows that the microstructure of the RM is sparse, and the distribution of hydration products is uneven.